APLIKASI LIMBAH CAIR PABRIK KELAPA SAWIT DAN NPK ORGANIK PADA TANAMAN TIMUN SURI (Cucumis sativus L.) - Daniel Daniel; Siti Zahrah; Fathurrahman Fathurrahman (UIR Press, 2017)
The study aimed to determine the effect of interaction between palm oil mill and organic NPK liquid waste doses on the growth and production of Suri Cucumber plants. The design used in this study was a Factorial Completely Randomized Design consisting of 2 factors. The first factor is palm oil mill effluent with a dose of 0, 100, 200, 300 ml/plant while the second factor is organic NPK with a dose of 0, 5, 10, 15 grams/plant. The parameters observed were flowering age, age of the first harvest, number of fruit crops, the weight of fruit per fruit, weight of fruit per plant. The last observation data were analyzed statistically and continued with a BNJ follow-up test at the level of 5%. The results showed that interactively the administration of palm oil mill effluent and organic NPK fertilizer gave a significant effect on fruit weight per fruit and fruit weight per Suri cucumber plant. The best treatment is a combination of 300 ml/plant palm oil mill effluent and 15 g / plant organic NPK fertilizer (L3N3). The main effect of giving palm oil mill effluent has a significant effect on flowering age, harvest age, number of fruits per plant, fruit weight per fruit and fruit weight per Suri cucumber plant. The best treatment is by giving 300 ml/plant palm oil mill effluent (L3). The main effect of giving organic NPK fertilizer significantly affected flowering age, harvest age, number of fruits per plant, fruit weight per fruit and fruit weight per Suri cucumber plant. The best treatment is by administering 15 g of organic NPK / plant (N3).